"At the boundary of perceived reality and pure form" : establishing an authentic authorial voice in John Banville's 'The Sea' - Ong, Selina Kai Li (Nanyang Technological University, 2017)
This thesis seeks to demonstrate how John Banville’s use of form in The Sea helps fulfil the conditions set up in the novels preceding The Sea to navigate the irreconcilable gap between writing and the reality it attempts to represent. Faced with two systems – writing and objective reality – that exist independent of each other, John Banville has previously explored the impossibility of either system being integrated with the other by bending to rules that do not apply to it. In this thesis we will examine the problems that The Sea inherits from the novels preceding it and its attempt at postulating a solution by focusing on form and elements of writing. The main section of the thesis would involve a close reading of The Sea and an examination of how various narrative strategies are employed to recreate a more authentic authorial voice by giving up attempts at replicating objectively verifiable truths. Key ideas and strategies employed by artist Pierre Bonnard will be used as a conceptual framework to organise the close reading.